2000
DOI: 10.1089/10445490050043308
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Organization of the Human and MousestauGenes

Abstract: Mammalian Staufen is a double-stranded RNA-binding protein potentially involved in mRNA transport and localization. Recently, we reported that the human gene is located on chromosome 20, region q13.1. We now report the genomic organization of both the human and mouse stau genes. Amplification of genomic DNA and sequencing of the resulting PCR products indicated that the human and mouse genes are fragmented into 15 and 12 exons, distributed over at least 65 and 17 kb of genomic DNA, respectively. The three addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…A 55-kDa Staufen 1 and a 53-kDa Staufen 2 isoforms are expressed in these cells, in agreement with previously reported data in other cell types (Wickham et al, 1999;Kiebler et al, 1999;Brizard et al, 2000;Duchaine et al, 2000Duchaine et al, , 2002Monshausen et al, 2001). We found that both, Staufen 1 and Staufen 2 form granules that associate with the cytoskeleton in the tubulin as well as in the actin-rich domains of the myelinating processes.…”
Section: Discussionsupporting
confidence: 93%
“…A 55-kDa Staufen 1 and a 53-kDa Staufen 2 isoforms are expressed in these cells, in agreement with previously reported data in other cell types (Wickham et al, 1999;Kiebler et al, 1999;Brizard et al, 2000;Duchaine et al, 2000Duchaine et al, , 2002Monshausen et al, 2001). We found that both, Staufen 1 and Staufen 2 form granules that associate with the cytoskeleton in the tubulin as well as in the actin-rich domains of the myelinating processes.…”
Section: Discussionsupporting
confidence: 93%
“…2B). Similar genomic organization is observed in the human genome, suggesting that this phenomenon is conserved among mammals (6).…”
Section: Mstausupporting
confidence: 67%
“…The significance of the four different classes of transcripts is unknown. They arise by differential splicing since each of the inserts that appears in the 5Ј end of the cDNAs is flanked by large introns containing typical consensus splicing sequences (6). They are observed in all the tissues tested by RT-PCR, suggesting that they are not cloning artifacts.…”
Section: Discussionmentioning
confidence: 97%